2018
DOI: 10.4103/ija.ija_788_17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexmedetomidine for prevention of emergence agitation in patients posted for nasal surgery under desflurane anaesthesia: A prospective double-blinded randomised controlled trial

Abstract: Background and Aims:Nasal surgery under desflurane anaesthesia is more prone to develop emergence agitation (EA). The present study aimed to evaluate the efficacy of dexmedetomidine for prevention of EA.Methods:A total of 72 patients were randomised to group C and group D. Group C patients received placebo while group D patients received dexmedetomidine 1.0 μg/kg bolus followed by 0.4 μg/kg/h after induction of anesthesia. End tidal desflurane was adjusted to keep the bispectral index (BIS) 45–55. Study drug w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Sympatholytic property of dexmedetomidine provided lower systolic blood pressure during T1 min to T15 min of operation. Our finding was in accordance with studies that found a significant reduction in hemodynamic status using dexmedetomidine ( 19 , 20 ). Also, Jae-Wook et al ( 21 ) demonstrated that dexmedetomidine has sympatholytic effects and it is used for sedative, anxiolytic, and analgesic purposes as an adjunct to several anesthetics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Sympatholytic property of dexmedetomidine provided lower systolic blood pressure during T1 min to T15 min of operation. Our finding was in accordance with studies that found a significant reduction in hemodynamic status using dexmedetomidine ( 19 , 20 ). Also, Jae-Wook et al ( 21 ) demonstrated that dexmedetomidine has sympatholytic effects and it is used for sedative, anxiolytic, and analgesic purposes as an adjunct to several anesthetics.…”
Section: Discussionsupporting
confidence: 93%
“…One of the most common problems in the recovery ward is delayed recovery and longer discharge time of patients receiving pre-operative or intra-operative dexmedetomidine infusion. ( 19 , 21 , 22 ) In our research, the duration of the recovery ward stay was significantly longer in the DA group than in the KA group. However, two groups were similar in terms of total anesthesia time and awakening time.…”
Section: Discussionmentioning
confidence: 43%
“…In elderly patients admitted to the ICU, dexmedetomidine contributes to improved sleep quality pattern, reduced delirium, increased survival up to 2 years, and improved cognitive function and quality of life in 3-year survivors 2527. Likewise, its intraoperative use has increased because it could reduce EA in pediatric patients after general anesthesia28 or in adults undergoing nasal surgery 9,11,12. However, evidence regarding the effects of dexmedetomidine on EA and recovery quality in adults after lung surgery is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have advocated the beneficial effects of intraoperative administration of dexmedetomidine for reducing the incidence of perioperative morbidities after nasal surgery, such as intraoperative bleeding, postoperative pain, and EA [13, 18, 19]. Considering the short length of CR surgery, an intraoperative infusion of dexmedetomidine as an anesthetic adjuvant may prolong the anesthesia and recovery time [20]. Previous studies have shown that a single -dose of dexmedetomidine, not as a premedication, is also effective in reducing EA and facilitating smooth extubation after pediatric adenotonsillectomy [10].…”
Section: Discussionmentioning
confidence: 99%